How do chronotype and sleep patterns impact young athletes’ aerobic performance during Ramadan intermittent fasting? - El-Jaziz, A.; Lotfi, S. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Ramadan observance has been practiced by many faith groups and cultures worldwide. Moreover, recently, it has been adopted as a natural alternative to promote public health. During Ramadan, our circadian rhythm can be altered. This study investigates how athletes’ chronotype and sleep patterns impact aerobic fitness during Ramadan intermittent fasting. Study design. A prospective cohort design with repeated measurements was adopted. We measured the chronotype, maximal Oxygen Uptake as a measure of aerobic performance, and sleep patterns before and during Ramadan intermittent fasting. Then we explored the correlation among these variables. Methods. 50 amateur athletes (Mean age = 17.22 years SD = 1.15) from Morocco participated in this study. The maximal Oxygen Uptake was measured with the 20-m shuttle-run test. The chronotype was assessed by the Morningness-Eveningness Questionnaire. The sleep timing was assessed by Sleep Timing Questionnaire. We also assessed sleep quality with the Pittsburgh Sleep Quality Index. We examined the difference between variable means before and during Ramadan, also considering chronotype and sleep patterns of participants. Results. The results showed a significant decrease in sleep quality and maximal Oxygen Uptake during the Ramadan Intermittent Fasting. Also, we found a significant correlation between the chronotype, time in bed and time spent asleep. However, chronotype and sleep quality did not affect maximal Oxygen Uptake during the Ramadan intermittent fasting. Conclusions. Sleep and chronotype do not influence physical performance during Ramadan Intermittent Fasting. More research is needed to identify the leading cause of the drop in aerobic performance.